A study on trainee teachers of Faculty of Education, Universiti Teknologi MARA (UiTM) Shah Alam: understanding on cohesion and coherence in English writing / Nur Adila Mohd Yunus - Mohd Yunus, Nur Adila (2014)
Writing was seen as one of the most difficult skill to teach and learn, especially among second language learners. This research looked at a detrimental issue in Malaysian students' writing conventions which were; cohesion and coherence. The purpose of the study was to investigate the root of the problem; whether trainee teachers fully understood the two concepts in English writing. This research was drawn on the three major objectives; trainee teachers understanding on cohesion, coherence and possible ways for them to teach these structures to the students. This research has shown promising results for further researches and actions whereby trainee teachers did faced some trouble in identifying the two concepts. Furthermore, the information obtained throughout the research was vital in improving trainee teachers' knowledge and skills before they ventured to schools, which indicated that it was beneficial for other teachers, educators and even the Ministry of Education.